2014
DOI: 10.1177/0081246314546346
|View full text |Cite
|
Sign up to set email alerts
|

Gender and hardiness as predictors of career adaptability: an exploratory study among Black call centre agents

Abstract: The call centre career poses developmental challenges that require high levels of hardiness and career adaptability. This article explores whether call centre agents' gender and hardiness significantly and positively predicted their career adaptability, and whether women and men differed significantly regarding their hardiness and career adaptability. A cross-sectional survey was conducted with a sample of 409 early-career B l a c k African call centre agents (mean age = 32 years; 66% females). Correlations, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 35 publications
(70 reference statements)
1
25
0
7
Order By: Relevance
“…Call centre work is associated with minor room for progression and individual growth as vocational development is infrequent in such institutions (Coetzee & Harry, 2015). It is likely that a lack of growth and continuous development may result in boredom and in employee intentions to seek alternative employment elsewhere.…”
Section: Retention and Turnover In The South African Call Centre Indumentioning
confidence: 99%
See 2 more Smart Citations
“…Call centre work is associated with minor room for progression and individual growth as vocational development is infrequent in such institutions (Coetzee & Harry, 2015). It is likely that a lack of growth and continuous development may result in boredom and in employee intentions to seek alternative employment elsewhere.…”
Section: Retention and Turnover In The South African Call Centre Indumentioning
confidence: 99%
“…Döckel et al (2006) emphasised the importance of work-life balance policy by indicating that a flexible work scheduling is necessary, with policies allowing periods away from work for employees to take care of their family matters. Coetzee and Harry (2015) noted that high levels of hardiness and career adaptability are significant aspects that call centre agents can use to balance their lives and their demanding work life. Hardiness is regarded as a set of stress-resilient personality characteristics, whilst career adaptability is the ability to adjust to the working prescriptions and demands of call centre environment (Coetzee & Harry, 2015).…”
Section: Retention and Turnover In The South African Call Centre Indumentioning
confidence: 99%
See 1 more Smart Citation
“…However, Kanten (2012) asserted that career adaptability levels of student's differ based on their gender, willingness to choice of graduate program and the planning to work in the graduated field or not and the social environment. Coetzee and Harry (2015) suggested that gender and hardiness are significant predictors of career adaptabilities. In addition, Kadir and Deniz (2016) found out career adaptability levels of student's differ based on whether young adults made their departmental choice consciously and they have previous education or training.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Exercise techniques contribute to the body's knowledge of the nature of academic hardiness, which can help in developing a better understanding of the variables that affect academic achievement and academic outcomes, such as the success and fulfillment of future work (Coetzee & Harry, 2014). Excersises technique is a method of service in group guidance in the process of Guidance and Counseling.…”
Section: Introductionmentioning
confidence: 99%